Comparative efficacy between Livolin forte® and Ocimum gratissimum on CCl 4 induced Liver damage in Wistar albino Rats. - Ighodaro, C.N. * , Ebo, O.E. and Agoreyo, F. (Sokoto Journal of Medical Laboratory Science)
In recent years, the incidence of liver disease has remained an important public health problem worldwide despite global attention to eradicate it. Both Livolin forte® (LIV) and extract of Ocimum gratissimum have been used separately as hepatoprotective agent. The aim of this study was to compare the efficacy of Livolin forte® and Ocimum gratissimum at ameliorating liver damage. Twenty-four albino Wistar rats weighing between 150-200 g were used. They were randomly distributed into six groups (6) comprising four animals in each group. Group 1 rats (normal control) received 0.3 ml/kg/day of propylene glycol, the vehicle in which LIV was dissolved, orally for 4 weeks. Group 2 (toxic) received CCl 4 , dissolved in olive oil (1:1 v/v) at 0.7 ml/kg for 7 alternating days, so as to induce liver damage. Group 3 (standard) were pre-treated as group 2 after which they received oral administration of Livolin forte® at 5.2 mg/kg for 4 consecutive weeks and Group 4, 5 and 6 were pre-treated as group 2 and thereafter received oral graded doses of the extract at 100 mg/kg, 200 mg/kg and 400 mg/kg respectively for 4 consecutive weeks. The result showed that Livolin forte® group, pretreated with CCl 4 (Group 3) has a lower level of Serum Bilirubin, AST, ALT and ALP when compared with the extract of Ocimum gratissimum treated groups (Group 4, 5 and 6). However, this was statistically significant (p>0.05). In conclusion, Livolin forte® was better as a curative agent than Ocimum gratissimum extract in rats. It showed a higher level of efficacy on CCl 4 induced liver damage. This supports the use of the drug for treating hepatic damage in humans.